Aortic Valve-in-Valve in Externally Mounted Bioprosthesis: A Safe Treatment Option for Bioprosthetic Structural Valve Dysfunction. Issue 3 (May 2018) - Cheung, Anson W.; Ye, Jian; Dvir, Danny; Wood, David A.; Webb, John G.
Abstract : Objective: Aortic valve-in-valve implantation for prosthetic valve dysfunction is a good alternative to reoperative valve replacement. There are some limitations to this approach including the risk of coronary occlusion, patient prosthesis mismatch, and valve malposition. The incidence of coronary occlusion is higher in aortic valve-in-valve than de novo aortic stenosis cases. Multiple factors can contribute to this complication, and the type of bioprosthesis has been implicated. Methods: We examined our experience of 80 aortic valve-in-valve cases with internally and externally mounted leaflet valves. Results: Procedural success was achieved in 95% of cases with an overall 30-day mortality of 1.3%. Clinical and procedural outcomes were similar in the both cohorts. Conclusions: Our data suggest that aortic valve-in-valve implantation can be safely performed in carefully selected patient with internally and externally mounted leaflet bioprosthesis.